Electrospun laponite-doped poly(lactic-co-glycolic acid) nanofibers for osteogenic differentiation of human mesenchymal stem cells - Wang, Shige (2019)
We report the fabrication of uniform electrospun poly(lactic-co-glycolic acid) (PLGA) nanoﬁbers incorporated with laponite (LAP) nanodisks, a synthetic clay material for osteogenic differentiation of human mesenchymal stem cells (hMSCs). In this study, a solution mixture of LAP suspension and PLGA was electrospun to form composite PLGA–LAP nanoﬁbers with different LAP doping levels. The PLGA–LAP composite nanoﬁbers formed were systematically characterized via different techniques. We show that the incorporation of LAP nanodisks does not signiﬁcantly change the uniform PLGA ﬁber morphology, instead signiﬁcantly improves the mechanical durability of the nanoﬁbers. Compared to LAP-free PLGA nanoﬁbers, the surface hydrophilicity and protein adsorption capacity of the composite nanoﬁbers slightly increase after doping with LAP, while the hemocompatibility of the ﬁbers does not appreciably change. The cytocompatibility of the PLGA–LAP composite nanoﬁbers was assessed by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay of L929 mouse ﬁbroblasts and porcine iliac artery endothelial cells cultured onto the surface of the nanoﬁbers. The results reveal that the incorporated LAP is beneﬁcial to promote the cell adhesion and proliferation to some extent likely due to the improved surface hydrophilicity and protein adsorption capability of the ﬁbers. Finally, the PLGA–LAP composite nanoﬁbers were used as scaffolds for osteogenic differentiation of hMSCs. We show that both PLGA and PLGA–LAP composite nanoﬁbers are able to support the osteoblast differentiation of hMSCs in osteogenic medium. Most strikingly, the doped LAP within the PLGA nanoﬁbers is able to induce the osteoblast differentiation of hMSCs in growth medium without any inducing factors. The fabricated smooth and uniform organic–inorganic hybrid LAP-doped PLGA nanoﬁbers may ﬁnd many applications in the ﬁeld of tissue engineering.